THE IMPACT MODELS OF ENTREPRENEURSHIP EDUCATION PROGRAMS AND STUDENTS’ INDIVIDUAL ATTITUDES ON STUDENTS’ ENTREPRENEURIAL INTENTIONS - Albertus Daru Dewantoro; Lucia Ina Trisjanti; Diio Rivaldo (Universitas Ahmad Dahlan Indonesia, 2020)
Generating unemployment is something that is not desired by every university. The history of the economy in Indonesia proves that entrepreneurship has a positive impact on the resilience and economic growth of the nation, therefore most universities require their students to take entrepreneurship courses. University academic support in terms of entrepreneurship education is expected to be able to foster students entrepreneurial intentions, so that the target of increasing the number of entrepreneurs can be realized. Entrepreneurial intention is also influenced by individual students attitudes factors. This research was conducted by surveying 155 students at two universities in Surabaya, to answer the purpose of this study we use the analysis of independent sample test and multiple regression. This study found evidence that the type of education (vocational and non-vocational), and the background of parents' work (entrepreneurial and non-entrepreneurial professions) did not have a significant difference affecting students entrepreneurial intentions. This study also found evidence that factors of students individual attitudes and entrepreneurship education programs had a positive and significant effect on growing students entrepreneurial intentions